2012
DOI: 10.1108/09564231211226105
|View full text |Cite
|
Sign up to set email alerts
|

Coping with customer aggression

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 90 publications
1
44
0
Order By: Relevance
“…The tactics include ignoring difficult customers, bribing customers, using emotional labors, exploiting sexual attractiveness, eliciting support from patrons, altering personal speech patterns, and manipulating the servicescape (e.g., open the windows). Goussinsky (2012) suggested three coping strategies to deal with customer verbal aggression: behavioral disengagement, seeking emotional support, and venting negative emotions. It was also found that frontline employees are less motivated to solve the problems raised by dysfunctional customers due to the perceived injustice in the interpersonal interactions (L. C. Harris & Reynolds, 2003).…”
Section: Frontline Employees' Responses To Iccbmentioning
confidence: 99%
“…The tactics include ignoring difficult customers, bribing customers, using emotional labors, exploiting sexual attractiveness, eliciting support from patrons, altering personal speech patterns, and manipulating the servicescape (e.g., open the windows). Goussinsky (2012) suggested three coping strategies to deal with customer verbal aggression: behavioral disengagement, seeking emotional support, and venting negative emotions. It was also found that frontline employees are less motivated to solve the problems raised by dysfunctional customers due to the perceived injustice in the interpersonal interactions (L. C. Harris & Reynolds, 2003).…”
Section: Frontline Employees' Responses To Iccbmentioning
confidence: 99%
“…Boundary employees are usually subjected to high functional and emotional demands from interactions with customers, with implications in terms of burnout and health (e.g. Goussinsky, 2012;Salanova et al, 2005). In addition, when employees perceive unfairness from their customers, outcomes can be negative even for organizations, for example, by increasing sabotage (Skarlicki et al, 2008) or negative word of mouth by employees.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…When customer mistreatment subjugates FLEs, it can lead to feelings of degradation, humiliation and loss of face with consequent negative impact on one’s psychological well-being (anxiety, emotional exhaustion), diminished job performance and heightened turnover intentions (Grandey et al , 2004; Harris and Reynolds, 2003; Karatepe et al , 2009; Akkawanitcha et al , 2015). The effects of customer aggression on FLEs’ face loss and consequent psychological well-being thus constitute a crucial point for consideration with Goussinsky (2012) calling it “the dark side” of customer service roles.…”
Section: Introductionmentioning
confidence: 99%